Analysis of functional image analysis contest (FIAC) data with brainvoyager QX: From single-subject to cortically aligned group general linear model analysis and self-organizing group independent component analysis - Goebel, Rainer; Esposito, Fabrizio; Formisano, Elia (Human brain mapping, 2006)
The Functional Image Analysis Contest (FIAC) 2005 dataset was analyzed using BrainVoyager QX. First, we performed a standard analysis of the functional and anatomical data that includes preprocessing, spatial normalization into Talairach space, hypothesis‐driven statistics (one‐ and two‐factorial, single‐subject and group‐level random effects, General Linear Model [GLM]) of the block‐ and event‐related paradigms. Strong sentence and weak speaker group‐level effects were detected in temporal and frontal regions. Following this standard analysis, we performed single‐subject and group‐level (Talairach‐based) Independent Component Analysis (ICA) that highlights the presence of functionally connected clusters in temporal and frontal regions for sentence processing, besides revealing other networks related to auditory stimulation or to the default state of the brain. Finally, we applied a high‐resolution cortical alignment method to improve the spatial correspondence across brains and re‐run the random effects group GLM as well as the group‐level ICA in this space. Using spatially and temporally unsmoothed data, this cortex‐based analysis revealed comparable results but with a set of spatially more confined group clusters and more differential group region of interest time courses. Hum. Brain Mapp, 2006. © 2006 Wiley‐Liss, Inc.